A percepção de discriminação do estudante no ambiente de ensino da medicina está associada ao seu sofrimento mental? resultados de estudo transversal - Rocha, Giovanna Ribeiro Gontijo da (2025)
Students’ perceptions of the educational environment are determinants of their behavior. Therefore, students with positive perceptions are more likely to develop more favorable approaches to learning. Negative aspects of the educational environment, such as discrimination, influence students’ perceptions and have repercussions on the emotional development of future doctors. This study aimed to investigate whether medical students’ personal perception of discriminatory experiences are associated with worse levels of mental health. This is a cross-sectional quantitative analytical study conducted at the Undergraduate Medical School of Universidade Federal de São João del Rei campus Centro-Oeste, and targeted 314 students from the 1st to the 12th period. Data collection was conducted from February to June 2023 through self-administered online questionnaires, composed of questions related to individual, socio-academic and academic environment characteristics. The experience of discrimination was measured by responses to questions on the Everyday Discrimination Scale, and the occurrence of probable cases of common mental disorders (CMD) was estimated using the General Health Questionnaire (GHQ-12). Stratified descriptive data analysis was performed to assess differences between groups, and logistic regression was used to estimate the magnitude of associations. It was observed that 38% of students reported moderate or high frequency of at least one discriminatory experience, and 32.6% were screened positively for the presence of psychological distress. The groups with the highest frequency of CMD were obese students, those who rarely participate in leisure and social activities, those who report experiences of discrimination (57.4%), and students with disabilities (50%). The independente factors associated with positive screening for CMD were being female and being in clinical cycle. Satisfaction with one's own appearance and socialization were protective factors. The results of this study highlight the vulnerability of certain subgroups, for which specific interventions should be considered.